The effects of service quality dimensions and passenger characteristics on passenger's overall satisfaction with an airport - Bezerra, George C. L. (2015)
The objective of this paper is twofold. First, to identify service quality dimensions related to airports. Second, to examine the effects of those dimensions on passenger's overall satisfaction with an airport together with variables related to passenger characteristics. Data from an extensive survey applied in a main Brazilian international airport were used. Exploratory factor analysis was applied to extract dimensions of airport service quality as perceived by the passengers. The effects on the overall satisfaction level were estimated using a probabilistic approach. Findings underline implications regarding the use of meaningful service dimensions instead of a large set of variables as predictors of passenger satisfaction. Moreover, the study stresses the need for considering how passenger characteristics may be related to different perceived levels of service quality.